Wastewater Treatment by Using Fruit Waste Derived Adsorbents - qizi, Kholdarova Gulsanam Akramjon (European Journal of Life Safety and Stability (2660-9630), 2022)
Numerous studies have been reported to find the applications of fruit-based waste materials for wastewater treatment, and several advanced composite materials with fruit waste have been engineered for specific applications. There are various wastes of fruits such as peels, shell and hulls, pulp, stalk, seeds, bunch, pomace, etc. These wastes come with different elemental compositions and inherent structures and morphologies, which ultimately affect the product. Moreover, among different fruit waste derived adsorbents, the fruit waste peels are considered as promising fruit waste sources for the development of bio-adsorbents due to their high lignocellulosic properties, which facilitate in high elemental composition of carbon. Furthermore, it is found that the use of peels as absorbents can help to adsorb the heavy metals due to presence of polar-organic compounds, which result in formation of chelate with metal ions. Therefore, since the year of 2000, the research interest on fruit peels derived bio-adsorbents has been on the rise gradually.